Benefits of SGLT2 inhibitors in arrhythmias - Gao, Jinghan; Xue, Genlong; Zhan, Ge; Wang, Xinying; Li, Jiatian; Yang, Xiaolei; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2022)
Some studies have shown that sodium-glucose cotransporter (SGLT) 2 inhibitors can definitively attenuate the occurrence of cardiovascular diseases such as heart failure (HF), dilated cardiomyopathy (DCM), and myocardial infarction. With the development of research, SGLT2 inhibitors can also reduce the risk of arrhythmias. So in this review, how SGLT2 inhibitors play a role in reducing the risk of arrhythmia from the perspective of electrical remodeling and structural remodeling are explored and then the possible mechanisms are discussed. Specifically, we focus on the role of SGLT2 inhibitors in Na+ and Ca2 + homeostasis and the transients of Na+ and Ca2 +, which could affect electrical remodeling and then lead to arrythmia. We also discuss the protective role of SGLT2 inhibitors in structural remodeling from the perspective of fibrosis, inflammation, oxidative stress, and apoptosis. Ultimately, it is clear that SGLT2 inhibitors have significant benefits on cardiovascular diseases such as HF, myocardial hypertrophy and myocardial infarction. It can be expected that SGLT2 inhibitors can reduce the risk of arrhythmia.